Progression of untreated gastric and pulmonary metastasis in a patient with resected acral melanoma. Issue 3 (9th March 2022) - Chawla, Gurasees S; Tolu, Seda S; Arora, Shitij
Abstract : We report a man in his 80s who presents with epigastric abdominal pain and fatigue for 2 weeks. His medical history was significant for left toe acral melanoma (excised 6 years prior) and a lung mass, further workup for which was declined at the time by the patient. On presentation, he had iron deficiency anaemia and esophagogastroduodenoscopy revealed a gastric mass. Histopathological analysis of gastric and subsequently, pulmonary, lesions were consistent with metastatic melanoma. This case demonstrates the unique slow progression of untreated pulmonary metastasis in metastatic melanoma.